2007
DOI: 10.1093/toxsci/kfm065
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomic Study of Triazole Fungicides and Perfluoroalkyl Acids in Rat Livers Predicts Toxicity and Categorizes Chemicals Based on Mechanisms of Toxicity

Abstract: Toxicogenomic analysis of five environmental chemicals was performed to investigate the ability of genomics to predict toxicity, categorize chemicals, and elucidate mechanisms of toxicity. Three triazole antifungals (myclobutanil, propiconazole, and triadimefon) and two perfluorinated chemicals [perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS)] were administered daily via oral gavage for one, three, or five consecutive days to male Sprague-Dawley rats at single doses of 300, 300, 175, 20, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
89
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(102 citation statements)
references
References 35 publications
11
89
2
Order By: Relevance
“…Previous studies reported that certain PFCs, such as PFOA, PFDA, and PFDoA decreased serum testosterone level in rats under toxicological dosages (Bookstaff et al, 1990;Martin et al, 2007;Shi et al, 2007Shi et al, , 2009). The serum PFCs concentrations (5 μg/mL to 260 μg/mL) measured in those dosed animals were in the same range as the concentrations of FTOHs applied to H295R cells in this study Martin et al, 2007). It has been shown that exposure to 6:2 FTOH or 8:2 FTOH significantly disrupted plasma concentrations of sex steroids in zebrafish with a LOEC of 30 μg/L for both chemicals (Liu et al, 2009a,b).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies reported that certain PFCs, such as PFOA, PFDA, and PFDoA decreased serum testosterone level in rats under toxicological dosages (Bookstaff et al, 1990;Martin et al, 2007;Shi et al, 2007Shi et al, , 2009). The serum PFCs concentrations (5 μg/mL to 260 μg/mL) measured in those dosed animals were in the same range as the concentrations of FTOHs applied to H295R cells in this study Martin et al, 2007). It has been shown that exposure to 6:2 FTOH or 8:2 FTOH significantly disrupted plasma concentrations of sex steroids in zebrafish with a LOEC of 30 μg/L for both chemicals (Liu et al, 2009a,b).…”
Section: Discussionmentioning
confidence: 94%
“…After culture for 24 h, cells were exposed to 0, 7.4, 22.2 or 66.6 μM 8:2 FTOH dissolved in dimethyl sulfoxide (DMSO; Sigma) for 24 h. Control treatments received 0.1% DMSO (v/v). The exposure concentrations were chose based on the information from previous studies Martin et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, Dio1 gene expression has also been shown to respond to changes in circulating levels of THs (Burmeister et al, 1997). Martin et al (2007) showed that PFOS caused significant Dio1 repression, concordant with significant total T 3 decreases in rats. In fish, Wei et al (2008) found that exposure of rare minnows (Gobiocypris rarus) to perfluorooctanoic acid (PFOA) significantly suppressed the gene expression of Dio2.…”
Section: Discussionmentioning
confidence: 98%
“…Benzimidazole and triazole derivatives are well known corrosion inhibitors that showed more than 97% of inhibition against acid corrosion of mild steel [4], but they are also known for their toxicity [5,6,7]. Notably, the toxic nature of the known effective inhibitors of arsenate-and chromate-based has necessitated the search for an alternative inhibitor that would not only be efficacious but environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%